The Research Progress on China Major Minority Detoxification Methods - Wang, Lei; Yu, Ze-Pu; Liu, Li-Song; Wang, Wei-Li; Yan, Han-Wen; Duan, Xiao-Hua (International Journal of Biotechnology for Wellness Industries, 2015)
Based on the research and material—sorting in recent decades involving Tibetan medicine Mongolia medicine Dai medicine Zhuang medicine Yao medicine, Yi medicine, Miao medicine, Jinuo medicine. Tibetan medicine has a unique system of medical theory, which posits that poisoning incidents have close relation with rLung, nKhris-pa, Badkan three factors (namely three due to), which by adjusting three due to is balance and achieve detoxification. Mongolian medicine believes that there are five-element doctrine, cold and heat, the strength and size of detoxifying respectively. "Disease first solution, the solution after the first treatment," Dai medicine "Yajie" theory and the series of Yajie (antidote)", which play a role in detoxification lies. Zhuang medicine theory includes "virtual drug-induced diseases," the etiology and pathogenesis. By correcting the bias by that bias, in order to achieve the purpose of detoxification. Yao medical theory: the Profit and Loss Balance Theory, the Cause Theory, which are related to detoxification. According to the theory of three gas, toxin factor theory as the core contents of Yi medical theory, which the application of detoxification method is associated with. Miao medicine thinks Poison for all ills, highlight the dispel toxin factor to the poison thery of nine. Jinuo medicine is fully application of national folk-detoxification plant and animal medicines, achieve the purposes of detoxification. In this review, we summarized the major approaches applied for detoxification methods by different ethnic groups in order to provide better guide for clinical practice of food, drugs, poisons and other toxics. This work provides also potential clinical application to open up a new way of thinking and new perspective for detoxification therapy based on the accumulated knowledge in traditional Chinese medicine.